Real exchange rate misalignment and currency crisis in Zimbabwe - Masunda, Stein (Scholarlink Research Institute Journals, 2016)
The sought to establish the role of the real exchange rate misalignment, particularly overvaluation in explaining currency crisis in Zimbabwe. Using annual data from 1980 – 2006 we established the determinants of real exchange rate misalignment and estimated the extent to which the exchange rate was misaligned. Using a dynamic ordinary least Squares (DOLS), the results of the empirical test supports the idea that re4al exchange rate misalignment in Zimbabwe was attributed to pressures exerted by government consumption, openness, excess credit , technical progress and capital flows. The calculated measure of real exchange rate misalignment was then used as a covariate in the currency crises model. Employing the logit and probit model, we estimated the extent to which real exchange rate misalignment (overvaluation), contributed in currency crisis. The results of the empirical test confirms too, that real exchange rate overvaluation, output growth, external debt, political instability and a slackening in the monetary policy are responsible for currency crises in Zimbabwe. This study contributes in identifying the factors responsible for currency crises in developing countries like Zimbabwe.